Case-control study of pneumonia patients with Streptococcus anginosus group bacteria in their sputum. Issue 12 (December 2016) - Hirai, Jun; Sakanashi, Daisuke; Haranaga, Shusaku; Kinjo, Takeshi; Hagihara, Mao; Kato, Hideo; Suematsu, Hiroyuki; Yamagishi, Yuka; Fujita, Jiro; Mikamo, Hiroshige
Abstract: Background and objective: In recent years, Streptococcus anginosus group (SAG) bacteria are becoming increasingly recognized as important pneumonia-causing pathogens. Although several small studies have been reported, the features of SAG pneumonia remain unclear, because the identification of SAG from sputum cultures is not routinely performed in most microbiology laboratories. The aim of this study was to elucidate the clinical characteristics of SAG pneumonia. Patient and methods: This was a retrospective case-control study utilizing data obtained in our hospital between September 2009 and June 2016. We investigated 31 patients with SAG pneumonia (PWP), and also assessed the difference between the 31 PWP and 37 patients without pneumonia (PWOP) in whose sputum SAG was detected. Results: Seventy-one percent of the patients were men and the median age was 78 years in the PWP. Univariate analysis indicated that the PWP were significantly more often a bed-ridden ( p  < 0.01) with comorbid aspiration than were the PWOP ( p  < 0.05). Among the PWP, nursing and healthcare-associated pneumonia (NHCAP) was the more common type of pneumonia (54.8%). S. anginosus was detected significantly more frequently in sputum cultures of PWP than PWOP ( p  < 0.01), and multiple pathogens were detected more frequently in PWP ( p  < 0.01). Streptococcus constellatus was the most frequently detected pathogen in patients with a single bacterial infection. Empyema was observed only in patients with multiple bacteria. Conclusions: SAG should be recognized as important causative pathogens of pneumonia, particularly among elderly patients with underlying disease associated with aspiration. NHCAP was the more common type of SAG pneumonia in this study.